2018
DOI: 10.15835/nsb10410288
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Temperature and Chlorophyll Content are Effective Measures of Drought Stress Tolerance in Durum Wheat

Abstract: Durum wheat (Triticum durum L.) is used for the preparation of multiple food products, including pasta and bread. Its production is restricted due to diverse environmental stresses i.e. drought and heat stress. Here, comparative analysis of durum wheat varieties was done by studying canopy temperature depression (CTD) and chlorophyll content (CHL), yield and yield contributing traits to evaluate their performance under stress and low stress conditions. Twelve durum wheat genotypes were studied under stressful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…It has been reported that with increasing drought stress, canopy temperature increased. However, CTD decreased (i.e., the difference between Tc and Ta decreases or the Tc and Ta were close to each other) and foliar application with silicon increased CTD significantly in wheat (Jokar et al 2018). Our study indicated that the lower the CTD, the higher the yield, making it, consistent with the findings of some researchers (Mohammadi et al 2011).…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that with increasing drought stress, canopy temperature increased. However, CTD decreased (i.e., the difference between Tc and Ta decreases or the Tc and Ta were close to each other) and foliar application with silicon increased CTD significantly in wheat (Jokar et al 2018). Our study indicated that the lower the CTD, the higher the yield, making it, consistent with the findings of some researchers (Mohammadi et al 2011).…”
Section: Discussionsupporting
confidence: 90%
“…3). The water spenders have higher stomatal conductance and lose water through transpiration, whereas water savers have conservative water use on account of lower stomatal conductance or early closure of stomata and as such have hotter canopies (Sofi et al 2019).A strong positive association between grain yield of durum wheat and canopy temperature depression under moisture-stressed conditions was reported by Jokar et al (2018) indicating that lines which maintained cooler canopies produced higher yields. Thus, it may be suggested that cooler canopy temperature (high CTD) is an indication of enhanced capacity of a plant to take up soil moisture.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient of variation of CTD in different studies ranges from middle (10-14 % (Sharma P. et al, 2017;Jokar et al, 2018)) to high (26-43 % (Kumar et al, 2017;Sharma D. et al, 2018)). Dryland conditions make CTD values negative (Thapa et al, 2018) and increase genotypic differences (Pinto et al, 2010).…”
Section: Variation and Heritability Of Ctdmentioning
confidence: 99%